Work-life conflict and associations with work- and nonwork-related factors and with physical and mental health outcomes: a nationally representative cross-sectional study in Switzerland - Gutzwiller Felix; Hämmig Oliver; Bauer Georg (BMC, 2009)
Abstract Background The aim of the present cross-sectional study was to examine work- and nonwork- related factors and physical and mental health outcomes associated with combined time- and strain-based work-life conflict (WLC) among adult employees living and working in Switzerland as well as possible gender differences in this regard. Methods The data used for the study were taken from wave 6 of the nationally representative Swiss Household Panel (SHP) collected in 2004. The analysis was restricted to 4'371 employees aged 20 to 64 years. Trivariate crosstabulations and multivariate linear and logistic regression analyses stratified by gender were performed in order to calculate gender-specific prevalence rates (%), beta coefficients (β) and crude as well as multiple adjusted odds ratios (OR) as measures of association. Results Every eighth person (12.5%) within the study population has a high or very high WLC score. Prevalence rates are clearly above average in men and women with higher education, in executive positions or managerial functions, in full-time jobs, with variable work schedules, regular overtime, long commuting time to work and job insecurity. Working overtime regularly, having variable work schedules and being in a management position are most strongly associated with WLC in men, whereas in women the level of employment is the strongest explanatory variable by far, followed by variable work schedules and high job status (managerial position). In both men and women, WLC is associated with several physical and mental health problems. Employees with high or very high WLC show a comparatively high relative risk of self-reported poor health, anxiety and depression, lack of energy and optimism, serious backache, headaches, sleep disorders and fatigue. While overall prevalence rate of (very) high WLC is higher in men than in women, associations between degrees of WLC and most health outcomes are stronger in women than in men. Conclusion This important issue which up to now has been largely neglected in public health research needs to be addressed in future public health research and, if the findings are confirmed by subsequent (longitudinal) studies, to be considered in workplace health promotion and interventions in Switzerland as elsewhere.